Intracameral streptokinase to treat severe pupillary fibrin membrane after partial penetrating keratoplasty+ (Annals of Medical Research, 2021)
None
Keywords: s : Partial penetrating keratoplasty, Pupillary fibrin membrane, Streptokinase